Techno-economic assessment of novel hybrid energy storage control strategies for Dynamic Frequency Response. (30th November 2022) - Hutchinson, Andrew J.; Gladwin, Daniel T.
Abstract: Frequency Response services are a key part of the operation of the Great Britain (GB) Electricity Grid system. One of the most prevalent areas for energy storage deployment is in providing dynamic frequency response services. Battery Energy Storage Systems (BESSs) are the most deployed storage medium for this application, but are vulnerable to high cycle rates and degradation. Flywheel Energy Storage Systems (FESSs) are far more resilient to cycle based degradation and by co-locating them with a BESS they can extend the life of the battery cells and improve the overall Net Present Value (NPV) of the system. This paper presents for the first time a detailed techno-economic analysis of 7 novel control strategies for hybrid systems and performs an in depth techno-economic analysis on the 3 strategies that show the most potential for real world deployment. Crucially, it produces novel and wide ranging results on the utilisation of FESSs for this application, giving a clear and detailed account of the price that flywheel manufacturers will need to achieve for their products to be viable in this field for the first time. It is demonstrated how these novel control strategies can be designed and refined to maximise the technical performance with a subsequent techno-economic analysis conducted to assess the most promising control strategies effectiveness, and a novel investigation carried out into the minimum total capital cost (TCC) that a FESS needs be priced at to achieve to a positive NPV change under these control strategies. Under general conditions, the threshold TCC below which a positive NPV change is achieved is between £550/kW and £5, 855/kW for the various control strategies and FESS configurations, showing that a wide range of different FESSs can be economically viable under the correct control strategy. Highlights: Flywheels can improve the performance of a Battery providing a frequency response service. Appropriate control of the Hybrid Energy Storage System is essential. Correct control settings can extract significant economic gains. Flywheels can be effective up to a cost of £5, 855/kW.